Malawi's farm input subsidy program: Where do we go from here? - Pauw, Karl; Thurlow, James (International Food Policy Research Institute, 2014)
Malawi’s Farm Input Subsidy Program (FISP) has dominated the agriculture and food security policy landscape in the country since its inception in 2005/06. FISP is now credited—or blamed, depending on one’s viewpoint— for a revival of agricultural input subsidies across Africa as a tool to raise crop productivity and reduce poverty and food insecurity. This follows global reporting about Malawi’s dramatic decline in food insecurity after implementing a subsidy program against expert advice. While historically the debate around the desirability of input subsidies tended to focus on whether short-term gains outweighed the long-term opportunity costs of forgone growth-enhancing investments in infrastructure, research, or extension services, a growing body of literature now questions the ability of these programs to even generate short-term, on-farm benefits that outweigh costs. Although discarding FISP may be political suicide in the short term, anecdotal evidence suggests a gradual but marked shift in Malawian public opinion about the effectiveness or even desirability of FISP. This note draws on the recent evaluation literature to identify key policy lessons so far, but also to highlight areas that require further analysis before policymakers can consider major reforms.